Math, asked by punith41, 1 year ago

-2+3/2y=-67/14 solve it by simple equations ​

Answers

Answered by jitekumar4201
1

Answer:

y = -\dfrac{7}{13}

Step-by-step explanation:

Given equation-

-2+\dfrac{3}{2y} =-\dfrac{67}{14}

\dfrac{3}{2y} = 2 - \dfrac{67}{14}

                 = \dfrac{14 \times2 - 67}{14}

                = \dfrac{28 - 67}{14}

\dfrac{3}{2y} = -\dfrac{39}{14}

Or, \dfrac{2y}{3} = -\frac{14}{39}

Or, 2y = -\dfrac{14 \times3}{39}

                 = -\dfrac{14}{13}

y =-\dfrac{14}{13 \times2}

y = -\dfrac{7}{13}

Similar questions